Implementasi Perjanjian Pekawinan Setelah Putusan Mahkamah Kontitusi Nomor 69/PUU-XIII/2015 di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Wuri Handayani; Indratirini Indratirini (Concept: Journal of Social Humanities and Education, 2024)
Marriage is something sacred and noble, marriage must be based on mutual trust and love between the two and carry out the rights and obligations as it should. In principle, this marriage agreement is the source of various forms of property in a marriage. The marriage agreement is made before the marriage takes place with the aim to make a deviation from the unity of the property unanimously between husband and wife provided that it does not conflict with the moral code. A marriage agreement is an agreement made by two prospective husband and wife before their marriage takes place, to regulate the consequences of a marriage involving wealth or outside it. The implementation of the marriage agreement after the Constitutional Court Decision Number 69 / PUU-XIII / 2015 at the Surabaya City Population and Civil Registry Service examines the procedural procedures before and after the decision and concerning the analysis of the implementation in the field relating to legislation and looking at the number of registrants in terms of This implication of the Constitutional Court Decision Number 69 / PUU-XIII / 2015 covers various matters both in the field or for related parties. Regarding the ratification of the marriage agreement it should still be carried out by the Registrar of Marriage even though the marriage agreement was made with a notarial deed so that no other party outside of the husband and wife is harmed later on.